(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Some thoughts have been raised about the configuration of the epigraphic culture during the Republican period in the areas where South-eastern Iberian script was used and the Roman influence on this process. To this aim, changes in epigraphic documents and the use of writing are analysed, trying to keep an overall vision in wich the expansion of the paleohispanic epigraphy and the appearance of the Latin one are two sides of the same historic process.